β-1,6-Glucan From Pleurotus eryngii Modulates the Immunity and Gut Microbiota - Wang, Xue; Qu, Yunhe; Wang, Yuan; Wang, Xiang; Xu, Jialei; Zhao, Hailing; Zheng, Donglin; Sun, Lin; Tai, Guihua; Zhou, Yifa; Cheng, Hairong (Frontiers in Immunology, 2022)
Polysaccharides from Pleurotus eryngii have a variety of biological activities. In the present study, a homogeneous branched β-1,6-glucan named APEP-A-b was obtained from the fruiting bodies of P. eryngii and the effects on immunity and gut microbiota were investigated. Our results showed that APEP-A-b could significantly increase phagocytic capacity of peritoneal cavity phagocytes, splenic lymphocyte proliferation, and NK cell activity. Furthermore, the proportion of CD4+ T cells and CD8+ T cells in lamina propria were significantly increased upon APEP-A-b treatment. Additionally, APEP-A-b supplementation demonstrated pronounced differentiating microbiota, which indicated by a promotion of the relative abundances of Lachnospiraceae and Rikenellaceae family etc.. Consistently, APEP-A-b significantly increased the concentration of acetic acid and butyric acid in the cecum contents. Collectively, our results suggest that β-1,6-glucan from P. eryngii might enhance the immunity by modulating microbiota. These results are important for the structure-activity relationship of polysaccharides as well as processing and product development of P. eryngii derived polysaccharides.